2014
DOI: 10.1016/j.rpor.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of physical parameters and determination of inflection point for Flattening Filter Free beams in medical linear accelerator

Abstract: a b s t r a c tBackground: Medical Linear accelerators manufactured without flattening filters are increas-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…Recently, there has been a growing interesting in operating medical linear accelerators without a flattening filter (FFF). The main advantages of FFF beams are increased dose rate, reduced scatter radiation, reduced leaf transmission and treatment head leakage 7 . Numerous literatures reported that the increased dose rate of FFF beams is particularly beneficial for stereotactic body radiotherapy (SBRT) due to reduction of the treatment times of large fraction doses [8.9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interesting in operating medical linear accelerators without a flattening filter (FFF). The main advantages of FFF beams are increased dose rate, reduced scatter radiation, reduced leaf transmission and treatment head leakage 7 . Numerous literatures reported that the increased dose rate of FFF beams is particularly beneficial for stereotactic body radiotherapy (SBRT) due to reduction of the treatment times of large fraction doses [8.9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of the current measurement is time consuming to apply a fine scanning step of 0.1 cm in the QA and commissioning process. MSM, techniques by Pönisch et al and the method of the re-normalization, which is a typical definition methods for the FFF beam field size, could contain uncertainty arising the scanning step [9,[15][16][17]. The uncertainty at the location of the inflection point may occur from the measured data for using less fine scanning step.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies to define the field sizes of a FFF beam [13,14]. The most representative method to determine the field size of the FFF beam is the use of the inflection point (IP) on the penumbra region of the beam's profile [15,16]. Nevertheless, there are some uncertainties to obtain correct IP from beam data measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The most representative method to determine the eld size of the FFF beam is the use of the in ection point (IP) on the penumbra region of the beam's pro le. [9,10] Nevertheless, there are some uncertainties in obtaining a correct IP from beam data measurement. To consider this uncertainty, Pönisch et al proposed a method to identify the IP at the eld edge of the FFF beam with the same level of the FF beam.…”
Section: Introductionmentioning
confidence: 99%